Learning Strategies at SMP Muhammadiyah 6 Krian During Covid-19 Pandemic - Rara Dewi Putri Rahmadani; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to determine the learning strategies implemented by the Muhammadiyah 6 Krian Junior High School in the midst of the Covid 19 pandemic and the obstacles in the application process. This study used a descriptive qualitative research method in which data was obtained by interview. documentation and observation around the school environment. During the Covid 19 pandemic, the government issued an online learning policy. Muhammadiyah 6 Krian Junior High School implements a learning strategy, namely learning online and offline. Teachers often face various kinds of obstacles when learning online. For that, the application of offline learning is also applied to optimize student learning.